EFEKTIFITAS INFOGRAFIS DALAM MEDIA PROMOSI UMKM - Andik Prakasa Hadi; Setiyo Adi Nugroho; Rudjiono Rudjiono; Sugiarto Sugiarto (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Taman Makam Abu Ambarawa is a cemetery managed by the Gotong Royong Social Foundation, has been using infographics in promotional media in the form of brochures, catalogs and business cards since 2017. This study was conducted to determine the effectiveness of using infographics in promotional media. The EPIC model is used as a method to determine the effectiveness of infographics in the promotional media that have been used, using the indicators of Empathy, Persuasion, Impact and Communication. Respondents in this study were people who had used the services of Taman Makam Abu Ambarawa. The results of this study indicate that the use of infographics in promotional media is very effective, with an EPIC index score of 3.38 indicating that the decision scale is very effective. While the tabulation of the EPIC and EPIC Rate dimensions indicated that the four dimensions of the EPIC model (empathy, persuasion, impact and communication) had a value greater than the minimum value of Very Effective of 3.25. This research can be used by stakeholder are related to cooperatives and UMKM, regarding the perspective of the use of infographics in promotional media that has proven to be effective, through the use of infographics to display products or services in promotional media for the cooperative development and UMKM.